2008
DOI: 10.1111/j.1365-2249.2008.03663.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil surface presentation of the anti-neutrophil cytoplasmic antibody-antigen proteinase 3 depends on N-terminal processing

Abstract: SummaryThe neutrophil serine protease proteinase 3 (PR3) is a main autoantigen in anti-neutrophil cytoplasmic antibody-associated vasculitis. PR3 surface presentation on neutrophilic granulocytes, the main effector cells, is pathogenically important. PR3 is presented by the NB1 (CD177) glycoprotein, but how the presentation develops during neutrophil differentiation is not known. An N-terminally unprocessed PR3 (proPR3) is produced early during neutrophil development and promotes myeloid cell differentiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 50 publications
(77 reference statements)
3
25
0
Order By: Relevance
“…High mPR3 expression is only found on those neutrophils that co-express the GPI-linked NB1 receptor (17,18,20). We performed previously ectopic expression studies showing that NB1 was a sufficient receptor for PR3 (18,35). Korkmaz et al (19) elegantly showed that a hydrophobic patch of the PR3 molecule mediates membrane binding via NB1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…High mPR3 expression is only found on those neutrophils that co-express the GPI-linked NB1 receptor (17,18,20). We performed previously ectopic expression studies showing that NB1 was a sufficient receptor for PR3 (18,35). Korkmaz et al (19) elegantly showed that a hydrophobic patch of the PR3 molecule mediates membrane binding via NB1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…For proteinase 3, an individual, possibly genetically encoded, pattern regulates expression in the absence of detectable stimuli [4]. Membrane expression of proteinase 3 depends on mature neutrophils on the CD177 glycoprotein and on partial processing of the amino terminus of the molecule [51].…”
Section: Factors Sustaining Inflammation In Small Vessel Vasculitismentioning
confidence: 99%
“…NB1 shows a bimodal distribution that superimposes with that of PR3 on purified blood neutrophils (Bauer et al, 2007). Active, mature forms of PR3 but not pro-PR3 can bind to the surface of NB1-transfected human embryonic kidney 293 cells (von Vietinghoff et al, 2008) and Chinese hamster ovary cells (Korkmaz et al, 2008b). Interaction involves the hydrophobic patch of PR3 because specific amino acid substitutions disrupting this patch in the closely related gibbon PR3 prevent binding to NB1-transfected cells (Korkmaz et al, 2008b).…”
Section: Plasma Membrane Associationmentioning
confidence: 99%